Impact of seed rate and time of sowing on rice fallow crops and their sustainable production system in machine-harvested rice fields - Jaya Singh, Devi Geethika; Elangovan, Subramanian; Paramasivam, Arunachalam; Arumugam, Gurusamy; Basir Ahmed, Bhakiyathu Saliha; Gurunathan, Selvarani; Krishnan, Jothilakshmi; Arumugam, Sathishkumar (Frontiers in Sustainable Food Systems, 2024)
A field experiment was conducted at the Department of Agronomy, Agricultural College and Research Institute, Tamil Nadu Agricultural University, Madurai to study the performance of rice fallow crops in machine-harvested rice fields. The primary objective of this study was to determine the optimal seed rate and the time of sowing rice fallow crops in machine-harvested rice fields. Rice fallow crop cultivation is the most significant low-cost production system in the delta region. However, the sustainability of the system is uncertain in the context of mechanical harvesting of rice using heavy machinery. The crops selected for the experimental trial were black gram (Vigna mungo (L.) Hepper.), sesame (Sesamum indicum), and proso millet (Panicum miliaceum). The field experiment was conducted using a strip plot design. Rice fallow crops were arranged in vertical plots, while various seed rates and sowing timings were arranged in horizontal plots. The results indicated that the sowing time and seed rate significantly influenced the growth and development of rice fallow crops in machine-harvested rice fields. On the day of rice harvest, a 20% increase in seed rate (36 kg ha−1) resulted in greater grain and straw yield among the black gram treatments. The increased seed rate compensated for the damage caused by mechanical harvesting on the day of the harvest when a combine harvester was utilized, increasing the yield and sustainability of the rice fallow crops.